دريدا والتراث القبالي: Derrida and the Kabbalistic Heritage - Ibrahim Elfida - الفيضا إبراهيم (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2018)
يهدف هذا البحث إلى إبراز حضور التصوف اليهودي الباطني "القبالي" في نتاج الفيلسوف اليهودي الفرنسي جاك دريدا، وذلك بدراسة العلاقة بين الأدب الفلسفي واللاهوت أولاً، ثم التعريف بالتصوف اليهودي الباطني المعروف باسم القبالة، ثم التعريف الموجز بجاك دريدا وبعض اللحظات المهمة في مسيرته. بعد ذلك، توقَّف البحث عند مقالين قيِّمين للدارسة سوزان هاندلمان، والباحث إليوت وولفسون، اللذينِ أكَّدا -على التوالي- تأثُّر دريدا بالتصوف القبالي وتقاطعه معه. وأخيراً، عرض البحث لمثال تطبيقي على ذلك الحضور القبالي في نص دريدا. This critical study seeks to highlight the influence and presence of the Jewish Mystical tradition, Kabbalah, in the work of the French Jewish philosopher Jacques Derrida. The study initially tries to study the relationship between philosophy, literature, and theology. Then, it provides a short biography of Derrida and a basic definition of the Kabbalah. The paper critically discusses two important works, by Susan Handelman and Elliot Wolfson, on the influence and convergence of Kabbalah and Derrida’s work. As a practical example the study shows the presence of Kabbalah in two passages from Derrida.